The use of the differential outcomes procedure for the recognition of facial expressions of complex emotions and its electrophysiological correlates - García-Pérez, Ángel; Carmona, Isabel; Estévez, Angeles F. (Frontiers in Psychology, 2024)
The differential outcomes procedure (DOP) is an easily applicable method for enhancing discriminative learning and recognition memory. Its effectiveness in improving the recognition of facial expressions of emotion has been recently explored, with mixed success. This study aims to explore whether the expectancies generated via the DOP are reflected as differences in event-related potentials (ERPs) between participants in differential (DOP) or non-differential conditions (NOP) in a facial expression of complex emotion label task. Participants (n = 27 total, 14 DOP) in the DOP group received a specific reward for each specific emotion, while those in the NOP group received a random reinforcer when they correctly identified the emotion. We did not find differences in participants’ accuracy or reaction time depending on group (DOP or NOP). These findings suggest that the DOP may not provide significant benefits for tasks involving labeling complex emotional expressions. However, differences in ERP components were observed between both groups. Specifically, the NOP group showed an increased Late Positive Component during encoding, fronto-central P300 during memory maintenance of facial stimuli, and frontal, fronto-central, and central P300 during retrieval. These ERPs, taken together, suggest that the task was more attentionally demanding for the NOP group. Additionally, some markers identified in previous ERP studies on the DOP were absent, indicating that the outcome expectancies may not have been fully generated. Finally, there were also interactions between the valence of the facial stimuli, participant group, and some of the potentials, such as N100 or N200 during encoding. These findings suggest that participants in the DOP group may have allocated more attentional resources to processing expressions of positive-valence emotions during earlier stages, possibly due to reward expectancy effects.